Comparación de soluciones CRM que apoyan en la mejora del control de la producción en la planta de Agua Caluma - López Zambrano, Jaritza Liseth (2021)
Nowadays knowing and satisfying the client's needs has become the fundamental objective in the work of companies. The Caluma Packaged Purified Water company has been presenting problems in the handling and access of its clients' information. The management of customer relationships, CRM is the set of business strategies. designed in order to build a lasting relationship with customers. During this investigation, it was possible to verify the lack of registration of customer information, where the lack of an efficient tool to develop daily processes was also evidenced. The proposal was made to design a business strategy for the Agua Caluma plant, due to the lack of registration of customer information, in order to broaden the theme and conceptualization of management tools such as CRM. This case study focuses on the quantitative and qualitative methodology, because it is proposed from theoretical and practical models and to evaluate the customer loyalty process and its internal processes to be more strategic in the management of the information that is collected and at the close of business.